Local ecological knowledge as source material for historical research. Reflections on interdisciplinary collaboration, politics and history through the Fávllis network and the Porsanger Fjord - Weines, Jørn (UiT Norges arktiske universitet, 2016)
Over the course of the past decades, local ecological knowledge (LEK) has become an increasingly present factor in policymaking and management in Norway and internationally. The effects of climate change are highly topical, which makes it important to explore the possibilities of LEK in all disciplines of the social sciences. The main research question of this thesis is: how can LEK be utilized as source material in historical research? This question has many facets and brings up reflections on interdisciplinary collaboration, history, politics and policy. These are explored through the cases of the Fávllis research network and the LEK material it gathered in the Porsanger Fjord in Northern Norway. Central in this is the points of contact between LEK and environmental history. The focus on is not on empirical analysis but on theory and methodology. In answering the research question, the thesis accounts for the historiography of the LEK term and environmental history, and looks at several questions of epistemology, methodology and practical use, as well as differences in portrayals of the Porsanger Fjord in various historical accounts.